An activated carbon-based CO adsorbent and preparation method thereof

By adding mesoporous filler and carbonizing in the preparation process of activated carbon-based CO adsorbent, the shortcomings of existing CO adsorbents in CO/CH4 selectivity are solved, and efficient CO/CH4 separation effect is achieved.

CN116474719BActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210045611.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-15
Publication Date
2025-03-04
Estimated Expiration
2042-01-15

AI Technical Summary

Technical Problem

The existing CO adsorbents have shortcomings in the adsorption selectivity of CO/CH4, and it is difficult to effectively separate the mixed gases containing CO.

Method used

By adding a mesoporous filler mixture during the preparation of activated carbon-based CO adsorbent and carbonizing during the calcination process, a high selective CO adsorbent loaded with cuprous chloride is formed.

Benefits of technology

The CO/CH4 selectivity of CO adsorbent is significantly improved, the CO adsorption amount reaches more than 40 mL/g, and the CO/CH4 selectivity reaches more than 10, which is suitable for the separation and purification of mixed gases containing CO.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses an activated carbon-based CO adsorbent and a preparation method thereof. The preparation method comprises the following steps: (1) uniformly mixing an activated carbon raw material and a copper salt precursor; (2) calcining the mixture obtained in step (1) under an inert atmosphere; (3) uniformly mixing the mixture obtained in step (2) with a mesoporous filler and a copper salt precursor; (4) calcining the mixture obtained in step (3) at a certain temperature to obtain a highly selective CO adsorbent loaded with cuprous chloride. The present invention improves the adsorption selectivity of the adsorbent for CO / CH4 by adding a mesoporous filler mixture during the preparation of the activated carbon-based adsorbent and performing in-situ carbonization. The adsorbent provided by the present invention has a CO adsorption capacity of more than 40 mL / g and a CO / CH4 selectivity of more than 10.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adsorption separation, and in particular relates to an activated carbon-based CO adsorbent and a preparation method thereof. Background Art

[0002] CO is an important chemical raw material that can be used to produce chemical products such as formic acid, acetic acid, and carbonates. At the same time, CO, as a gas impurity, is widely present in many chemical gases such as hydrogen, and CO has a poisoning effect on many catalysts. Therefore, it is necessary to separate CO from the gas for enrichment and utilization or remove it from the gas.

[0003] Common methods for separating CO include adsorption separation, cryogenic separation and solution absorption. Adsorption separation has been widely used due to its low energy consumption and high efficiency. The key to adsorption separation is the development of efficient adsorbents. Among CO adsorbents, the π-complex adsorption of CO by monovalent copper metal is often used to develop efficient adsorbents. Monovalent copper adsorbents have high selective adsorption for CO, but do not have π-complex effect for gases such as N2 and CH4. This effect can be used to separate and purify mixed gases containing CO.

[0004] When preparing a copper-based CO adsorbent, the copper metal precursor needs to be loaded on a porous carrier and further reduced to prepare a CO adsorbent loaded with monovalent copper. Commonly used porous carriers include activated carbon, molecular sieves, etc. Activated carbon-based CO adsorbents are widely used because of their advantages such as low cost and easy availability of carriers and certain reducibility of activated carbon itself.

[0005] Chinese patent CN108704609A discloses a method for preparing a monolayer CuCl / activated carbon adsorbent for CO adsorption and separation, wherein Cu2(OH)2CO3 and CuCl2 are dissolved in formic acid to obtain a divalent copper salt solution, which is then impregnated on the surface of activated carbon to obtain an adsorbent precursor; the precursor is then heated in a vacuum environment or in a flowing inert atmosphere of N2 or Ar to prepare a monolayer CuCl / activated carbon adsorbent. Although the adsorbent of this invention has a high CO / N2 adsorption selectivity, the CO / CH4 adsorption selectivity is not high. Summary of the invention

[0006] In order to overcome the shortcomings and deficiencies of the prior art, the present invention provides an activated carbon-based CO adsorbent and a preparation method thereof.

[0007] According to a first aspect of the present invention, the present invention provides a method for preparing an activated carbon-based CO adsorbent.

[0008] The method for preparing the activated carbon-based CO adsorbent of the present invention comprises the following steps:

[0009] (1) Mixing the activated carbon raw material and the copper salt precursor uniformly;

[0010] (2) calcining the mixture obtained in step (1) under an inert atmosphere;

[0011] (3) uniformly mixing the mixture obtained in step (2) with the mesoporous filler and the copper salt precursor;

[0012] (4) The mixture obtained in step (3) is calcined at a certain temperature to obtain a highly selective CO adsorbent loaded with cuprous chloride.

[0013] Furthermore, the activated carbon raw material in step (1) is selected from at least one of coal-based activated carbon, coconut shell-based activated carbon, wood-based activated carbon, etc., preferably coal-based activated carbon.

[0014] Furthermore, the mixing method in step (1) includes one of solid high-speed stirring mixing, grinding mixing, and solution mixing, preferably grinding mixing or solution mixing.

[0015] Furthermore, the copper salt precursor in step (1) is selected from at least one of cupric chloride and cuprous chloride, preferably cupric chloride. The copper salt precursor may be in the form of a solution or a solid.

[0016] Furthermore, in step (1), the mass ratio of the copper salt precursor to the activated carbon raw material is 5%-70% on a dry basis.

[0017] Furthermore, the calcination conditions in step (2) include: the calcination atmosphere is nitrogen, argon or the like; the calcination temperature is 150-500° C., preferably 200-450° C.; and the calcination time is 0.2-5 h, preferably 0.5-4 h.

[0018] Furthermore, the mesoporous filler in step (3) is selected from cyclic organic matter, chain organic matter, etc.

[0019] Furthermore, the cyclic organic compound in step (3) includes aromatic organic compounds, saturated cyclic organic compounds, etc., and the number of rings is 1 to 4, preferably 1 to 3.

[0020] Furthermore, the chain organic matter in step (3) includes unbranched chain organic matter, branched chain organic matter, etc., and the number of carbon atoms in the chain is 4 to 15, preferably 5 to 12.

[0021] Furthermore, the amount of the mesoporous filler used in step (3) is 1% to 50% of the weight of the solid obtained after calcination in step (2), preferably 3% to 45%, on a dry basis.

[0022] Furthermore, the copper salt precursor in step (3) is selected from at least one of cupric chloride solution and cuprous chloride solution, preferably cupric chloride solution.

[0023] The amount of the copper salt precursor used in step (3) is 5% to 60% by weight of the mesoporous filler added in step (3) on a dry basis, preferably 10% to 55%.

[0024] Furthermore, the mixing method in step (3) includes one of solid high-speed stirring mixing, grinding mixing, and solution mixing, preferably grinding mixing or solution mixing.

[0025] Furthermore, the calcination temperature in step (4) is 250-900° C., preferably 300-850° C.; the calcination time is 0.5-10 h, preferably 1-8 h.

[0026] Furthermore, the calcination atmosphere in step (4) is an inert atmosphere or a nitrogen atmosphere, so that the added mesoporous filler can be carbonized to achieve the purpose of filling the mesopores or macropores of the activated carbon.

[0027] According to a second aspect of the present invention, the present invention also provides an activated carbon-based CO adsorbent, which is prepared by the method described above.

[0028] Furthermore, the CO adsorption capacity of the CO adsorbent is above 40 mL / g, and the CO / CH4 selectivity is above 10. The CO adsorbent is particularly suitable for separation and purification of mixed gases containing CO.

[0029] Compared with the traditional CO adsorbent preparation technology, the present invention prepares a CO adsorbent with high CO / CH4 selectivity by adding a mesoporous filler mixture (including a mesoporous filler and a copper salt precursor) during the preparation process of the activated carbon-based CO adsorbent and carbonizing it in situ. The added mesoporous filler effectively fills the mesopores and macropores in the original activated carbon, further carbonizes it into activated carbon, reduces the adsorption of CH4 in the mesopores, and the copper salt loaded thereon can further increase the adsorption amount of CO, thereby greatly improving the selectivity of the adsorbent for CO / CH4 while maintaining a high CO adsorption amount.

[0030] Compared with the prior art, the beneficial effects of the present invention are:

[0031] 1. In the method of the present invention, firstly, the activated carbon raw material and the copper salt precursor are mixed and calcined according to the traditional method to obtain activated carbon loaded with copper salt; then, the solid mixture is mixed with the mesoporous filler and the copper salt precursor, so that the mesoporous filler enters the macropores or mesopores of the activated carbon to achieve the filling purpose. At the same time, the added copper salt precursor (especially the CuCl2 solution will enter the macropores or mesoporous channels of the activated carbon), and then in the subsequent carbonization and calcination process, more microporous channels are formed in the macropores or mesoporous channels of the activated carbon. In this process, the copper salt precursor will also be distributed and reduced on the surface of the carbon material formed by the mesoporous precursor, that is, the macropores and mesoporous channels are reduced, the micropores and specific surface area are increased, and the loading amount of Cu (I) is increased.

[0032] 2. Through the method of the present invention, on the one hand, the macropores and mesopores of the activated carbon are filled with small-pore carbon formed by carbonization of the mesoporous filler, thereby reducing the adsorption capacity of the activated carbon adsorbent for methane; on the other hand, while filling the macropores or mesopores, the newly loaded copper salt increases the adsorption capacity for CO. As a result, compared with conventional CO adsorbents, the activated carbon-based CO adsorbent provided by the present invention has a higher adsorption capacity and higher CO / CH4 selectivity. The CO adsorption capacity of the CO adsorbent provided by the present invention is above 40 mL / g, and the CO / CH4 selectivity reaches above 10. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with embodiments, but the present invention is not limited to the following embodiments. Without departing from the content and scope of the present invention, changes in implementation should be included in the technical scope of the present invention.

[0034] In the following examples and comparative examples, the activated carbon raw materials, copper salt precursors and mesoporous fillers used are all commercially available products. The adsorption of CO and CH4 by the obtained CO adsorbent is measured by a high-pressure adsorption instrument at 25°C, and the selectivity of the adsorbent for CO / CH4 is obtained by calculating the ratio of the CO adsorption to the CH4 adsorption under 1 bar.

[0035] Example 1

[0036] 80g coal-based activated carbon powder and 20g cuprous chloride were mixed evenly by mechanical grinding, and the resulting mixture was calcined at 400°C for 1h in a nitrogen atmosphere. The calcined material was ground and mixed evenly with 10g naphthalene and 2g cuprous chloride, and calcined at 450°C in a nitrogen atmosphere for 2h to obtain the target product.

[0037] Example 2

[0038] 70g coconut shell-based activated carbon powder was mixed with 30g copper chloride aqueous solution, and the mixture was calcined at 450°C for 1.5h in an argon atmosphere. The calcined material was mixed with 15g 1,4-ternaphthyl and 3g copper chloride solution, and calcined at 400°C in an argon atmosphere for 4h to obtain the target product.

[0039] Example 3

[0040] 75g of wood-based activated carbon powder and 25g of cuprous chloride were mixed evenly by mechanical grinding, and the resulting mixture was calcined at 300°C for 3.5h in a nitrogen atmosphere. The calcined material was ground and mixed evenly with 18g of anthracene and 5.4g of cuprous chloride, and calcined at 380°C in a nitrogen atmosphere for 3.5h to obtain the target product.

[0041] Example 4

[0042] 68g coal-based activated carbon powder was mixed with 32g copper chloride aqueous solution, and the mixture was calcined at 350°C for 3h in an argon atmosphere. The calcined material was mixed with 13g octane and 5.2g copper chloride solution, and calcined at 470°C in an argon atmosphere for 2.5h to obtain the target product.

[0043] Example 5

[0044] 65g coconut shell activated carbon powder and 35g cuprous chloride were mixed evenly by mechanical grinding, and the obtained mixture was calcined at 370°C for 2h in a nitrogen atmosphere. The calcined material was ground and mixed evenly with 20g hexane and 6g cuprous chloride, and calcined at 430°C in a nitrogen atmosphere for 4.5h to obtain the target product.

[0045] Example 6

[0046] 60g of wood-based activated carbon powder was mixed with 40g of copper chloride aqueous solution, and the mixture was calcined at 420°C for 2.5h in an argon atmosphere. The calcined material was mixed with 16g of p-xylene and 3.2g of copper chloride solution, and calcined at 400°C in an argon atmosphere for 2.3h to obtain the target product.

[0047] Comparative Example 1

[0048] 80 g of coal-based activated carbon raw powder and 20 g of cuprous chloride were mixed evenly by mechanical grinding, and the resulting mixture was calcined at 400° C. for 1 h under a nitrogen atmosphere to obtain the target product.

[0049] Comparative Example 2

[0050] 70 g of coconut shell-based activated carbon powder was mixed evenly with 30 g of copper chloride aqueous solution, and the resulting mixture was calcined at 450° C. for 1.5 h under an argon atmosphere to obtain the target product.

[0051] Comparative Example 3

[0052] 75 g of wood-based activated carbon raw powder and 25 g of cuprous chloride were mixed evenly by mechanical grinding, and the resulting mixture was calcined at 300° C. for 3.5 h under a nitrogen atmosphere to obtain the target product.

[0053] Comparative Example 4

[0054] 68 g of coal-based activated carbon raw powder was evenly mixed with 32 g of copper chloride aqueous solution, and the resulting mixture was calcined at 350° C. for 3 h under an argon atmosphere to obtain the target product.

[0055] Comparative Example 5

[0056] 65 g of coconut shell-based activated carbon powder and 35 g of cuprous chloride were mixed evenly by mechanical grinding, and the resulting mixture was calcined at 370° C. for 2 h under a nitrogen atmosphere to obtain the target product.

[0057] Comparative Example 6

[0058] 60 g of wood-based activated carbon raw powder was evenly mixed with 40 g of copper chloride aqueous solution, and the resulting mixture was calcined at 420° C. for 2.5 h under an argon atmosphere to obtain the target product.

[0059] Table 1 Adsorbent properties

[0060]

Claims

1. A method for preparing an activated carbon-based CO adsorbent, comprising the following steps: (1) Mixing the activated carbon raw material and the copper salt precursor uniformly; (2) calcining the mixture obtained in step (1) under an inert atmosphere; (3) uniformly mixing the mixture obtained in step (2) with the mesoporous filler and the copper salt precursor; (4) calcining the mixture obtained in step (3) at a certain temperature to obtain a highly selective CO adsorbent loaded with cuprous chloride; Wherein, the mesoporous filler is selected from at least one of naphthalene, 1,4-ternaphthalene, anthracene, octane, hexane, and p-xylene; The calcination temperature in step (2) is 150-500°C; the calcination temperature in step (4) is 250-900°C.

2. The preparation method according to claim 1, characterized in that: The activated carbon raw material described in step (1) is selected from at least one of coal-based activated carbon, coconut shell-based activated carbon and wood-based activated carbon.

3. The preparation method according to claim 1, characterized in that: The mixing described in step (1) includes one of solid high-speed stirring mixing, grinding mixing, and solution mixing.

4. The preparation method according to claim 1, characterized in that: The copper salt precursor in step (1) is selected from at least one of cupric chloride and cuprous chloride; the copper salt precursor is in the form of a solution or a solid.

5. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the copper salt precursor to the activated carbon raw material is 0.05-0.7:1 on a dry basis.

6. The preparation method according to claim 1, characterized in that: The calcination conditions in step (2) include: the calcination atmosphere is a nitrogen or argon atmosphere, and the calcination time is 0.2 to 5 hours.

7. The preparation method according to claim 1 or 6, characterized in that: The calcination conditions in step (2) include: a calcination temperature of 200-450° C. and a calcination time of 0.5-4 h.

8. The preparation method according to claim 1, characterized in that: The amount of the mesoporous filler used is 1% to 50% of the weight of the calcined solid obtained in step (2) on a dry basis.

9. The preparation method according to claim 8, characterized in that: The amount of the mesoporous filler used is 3% to 45% of the weight of the solid obtained after calcination in step (2) on a dry basis.

10. The preparation method according to claim 1, characterized in that: The amount of the copper salt precursor used in step (3) is 5% to 60% of the weight of the mesoporous filler added in step (3) on a dry basis.

11. The preparation method according to claim 10, characterized in that: The amount of the copper salt precursor used in step (3) is 10% to 55% of the weight of the mesoporous filler added in step (3) on a dry basis.

12. The preparation method according to claim 1, characterized in that: The mixing in step (3) includes at least one of solid high-speed stirring mixing, grinding mixing and solution mixing.

13. The preparation method according to claim 1, characterized in that: The calcination time in step (4) is 0.5 to 10 hours.

14. The preparation method according to claim 13, characterized in that: The calcination temperature in step (4) is 300-850°C, and the calcination time is 1-8 hours.

15. The preparation method according to claim 1, characterized in that: The calcination atmosphere in step (4) is an inert atmosphere, so that the added mesoporous filler can be carbonized.

16. An activated carbon-based CO adsorbent obtained by the preparation method according to any one of claims 1 to 15.

17. The activated carbon-based CO adsorbent according to claim 16, characterized in that: The CO adsorption capacity of the CO adsorbent is above 40 mL / g, and the CO / CH4 selectivity reaches above 10.

Citation Information

Patent Citations

  • Preparation method of monomolecular-layer CuCl / activated carbon adsorbent for CO adsorption separation

    CN108704609A

  • Preparation method for light alkane dehydrogenation catalyst with non-uniformly distributed active components

    CN103480359A

  • Preparation method of copper loaded activated carbon adsorbent

    CN103506070A